The impact of phosphorus enrichment on a Nitella sp. from sand-mine void wetlands, Capel, Western Australia - Annan, Isaac; John, Jacob (E Schweizerbart science publishers, 2012)
The disappearance of submerged macrophytes in shallow lakes is one of the most critical problems caused by eutrophication. The impact of increased phosphorus concentration on the establishment of a Nitella species as a suitable macrophyte for the rehabilitation of sandmine void wetlands at Capel in Western Australia, in the context of an imminent proposal to discharge effluent water from a waste processing plant into the wetlands was studied in the laboratory. The Nitella species was cultured in aquarium tanks in eutrophic and mesotrophic concentrations of phosphorus with a control (oligotrophic) treatment and its growth and lifecycle were monitored. It was observed that eutrophication had a significant impact on growth, morphology and lifecycle of Nitella. In addition to showing profuse vegetative growth, Nitella species produced no reproductive organs in the eutrophic medium. An approximate ratio of 1:1 male to female reproductive organs was recorded in the mesotrophic and control treatments but with reduced vegetative growth. Higher biomass of Nitella and filamentous algae including blue green algae was also recorded in the eutrophic treatment. In the eutrophic medium, the height, number of nodes, internode distance and the biomass were also found to be significantly higher than those in the other treatments. It was concluded that with the projected discharge of waste water into the Capel Wetlands, the Nitella meadows would display an initial accelerated growth followed by excessive growth of filamentous algae including cyanobacteria leading to increase in turbidity and eventual disappearance of Nitella species.